Primary Diffuse Large B-Cell Lymphoma of the Liver in a Patient with Sjogren Syndrome - Vadim Gorodetskiy; Wolfram Klapper; Natalya Probatova; Vladimir Vasilyev (Case Reports in Oncological Medicine)
Sjögren’s syndrome (SS) has the highest incidence of malignant lymphoproliferative disorders transformation among autoimmune diseases. We present a case of extranodal high grade lymphoma of the liver in a 52-year-old patient with long history of SS. Lymphoma manifested with sharp significant pain in the right hypochondrium, weakness, and profuse night sweats. Contrast-enhanced computed tomography scan (CT-scan) of the abdomen revealed multiple low density foci with homogeneous structure and clear contours in both lobes of the liver. Histologically, proliferation of medium sized lymphoma cells with round-oval and slightly irregular nuclei with fine chromatin was shown. Immunohistochemical and molecular features of the tumors allowed diagnosis of diffuse large B-cell lymphoma (DLBCL). To exclude secondary liver lesion by non-Hodgkin lymphoma, chest and small pelvis CT-scan, endoscopy of upper and lower gastrointestinal tract and study of bone marrow were performed. After 8 cycles of R-CHOP chemotherapy (rituximab, cyclophosphamide, doxorubicin, vincristine, and prednisone), the complete remission was achieved, which persists after 45 months of follow-up. Primary hepatic lymphomas are extremely rare, and previously only low-grade hepatic lymphomas have been described in SS. To our knowledge, the patient described here represents the first reported case of DLBCL with primary liver involvement in SS.